Pregunta
upstudy study bank question image url

Let \( f(x)=(x+1)^{2} \) Find a domain on which \( f \) is one-to-one and non-decreasing. Find the inverse of \( f \) restricted to this domain \( f^{-1}(x)=\square \)

Ask by Wade Warren. in the United States
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The domain where \( f(x) = (x + 1)^2 \) is one-to-one and non-decreasing is \( x \geq -1 \). The inverse function is \( f^{-1}(x) = \sqrt{x} - 1 \) for \( x \geq 0 \).

Solución

We begin with the function f(x) = (x + 1)². To have f be one-to-one and non-decreasing, we need to choose a domain on which the function is monotonic (either always non-decreasing or always non-increasing) and does not repeat values. 1. Observe that f(x) is a parabola that has its vertex where the derivative equals zero. Alternatively, note that the expression is a perfect square and reaches its minimum when x + 1 = 0, i.e. when x = -1. 2. For x ≥ -1, the function is non-decreasing (in fact, it is increasing) because as x increases from -1 onward, (x + 1) increases, and squaring a nonnegative number preserves the order. Thus, the domain on which f is one-to-one and non-decreasing is:   x ∈ [−1, ∞) Now, we find the inverse function f⁻¹(x) for x ≥ 0 (since f(x) = (x+1)² gives outputs in [0, ∞) when x ≥ -1). Start with:   y = (x + 1)² Solve for x:   √y = x + 1         (Since x + 1 ≥ 0 for x ≥ −1)   x = √y − 1 Thus, the inverse function is:   f⁻¹(y) = √y − 1 If we use x as the variable for the inverse function, then:   f⁻¹(x) = √x − 1 This gives the final answer:   f⁻¹(x) = √x − 1, for x ∈ [0, ∞).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To ensure that \( f(x) = (x + 1)^2 \) is one-to-one and non-decreasing, we can restrict the domain to \( x \geq -1 \). In this interval, the function is increasing, and each output corresponds to exactly one input. Now, to find the inverse of \( f \) on this domain, we set \( y = (x + 1)^2 \). Solving for \( x \), we get: 1. Take the square root: \( \sqrt{y} = x + 1 \) (and since we’re in the domain \( x \geq -1 \), we can use the positive root). 2. Rearranging gives \( x = \sqrt{y} - 1 \). Therefore, the inverse function is: \[ f^{-1}(x) = \sqrt{x} - 1 \]

Latest Pre Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad